Case of a Rarely Encountered Membranoproliferative Glomerulonephritis:Hepatitis C Associated Cryoglobulinemic Vasculitis - Tanış, Gülce; Dinçer, Mevlüt Tamer; Ak, Tümay; Polat, Ali Osman; Hürdoğan, Özge; Özlük, Yasemin; Seyahi, Nurhan; Trabulus, Sinan; Seyahi, Emire (Cerrahpaşa Medical Journal, 2025)
Cite this article as: Tanış G, Dinçer MT, Ak T, et al. Case of a rarely encountered membranoproliferative glomerulonephritis: hepatitis C-associated cryoglobulinemic vasculitis. Cerrahpaşa Med J 2025; 49, 0033, doi:10.5152/cjm.2025.24033